Modularization, standards, and technology - Kogeyama, Renato (2018)
Literature on modularity acknowledges its relevance to innovation, but it rarely addresses the relationship between modularity and the structure of competition in technological markets. In this dissertation, I seek to extend received wisdom by shedding light on this relationship, and I find that modularity affects the structure of competition by shifting the locus of value capture. An empirical test provides evidence that interfaces are pivotal for prevalence in technological markets due to the network effects created by the use of modularization at the component level, on the design stage. Also, I demonstrate that the location of modularity asymmetrically affects the performance of firms. Firms which adopt modular components performs better than firms that adopt proprietary components when horizontal differentiation is more important than vertical differentiation. Lastly, I examine the effect of participation in Standard Setting Organizations to job mobility and I find an unexpected consequence of competition in technological markets: participation in the standardization effort may inadvertently lead firms to leak intellectual capital due increased job mobility of their inventors.